Roxadustat has risks of reversible central hypothyroidism in patients undergoing hemodialysis: a single-center retrospective cohort study - Emiko Otsuka; Mineaki Kitamura; Satoshi Funakoshi; Hiroshi Mukae; Tomoya Nishino (Renal Failure)
Roxadustat, a hypoxia-inducible factor-prolyl hydroxylase inhibitor, has proven efficacy in the treatment of renal anemia; however, evidence indicates that it may cause central hypothyroidism. The prevalence and reversibility of roxadustat-induced central hypothyroidism in patients undergoing hemodialysis remain unclear. Here, we retrospectively analyzed thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) levels in 51 patients (mean age: 72.3 ± 10.7 years; 58.8% male) undergoing hemodialysis before, during, and after halting roxadustat treatment. TSH levels were significantly decreased from a median of 2.46 (interquartile range:1.60–4.51) mU/L before roxadustat treatment to 1.36 (0.72–2.41) mU/L during treatment (p < 0.001), and improved to 2.56 (1.78–4.63) mU/L after halting roxadustat (p < 0.001). Similarly, FT4 levels decreased from 1.11 (0.97–1.24) ng/dL before roxadustat treatment to 0.92 (0.71–1.03) ng/dL during treatment (p < 0.001) and improved to 1.05 (0.93–1.17) ng/dL after halting roxadustat (p < 0.001). FT3 levels were 2.04 (1.78–2.31) pg/mL before starting roxadustat, 1.97 (1.69–2.27) pg/mL during treatment, and 1.90 (1.63–2.18) pg/mL after halting roxadustat, with no significant difference between each group. Moreover, 2.0% of patients exhibited extremely low TSH levels (≤0.1 mU/L) and low TSH levels (>0.1 mU/L to <0.4 mU/L) before starting roxadustat and that percentage increased to 5.9% and 7.8%, respectively, during treatment. After roxadustat cessation, extremely low or low TSH levels recovered in all patients. Taken together, the results indicate that roxadustat can cause reversible central hypothyroidism in patients undergoing hemodialysis.